2002
DOI: 10.1038/sj.sc.3101282
|View full text |Cite
|
Sign up to set email alerts
|

The importance of posture on the isokinetic assessment of spasticity

Abstract: Our findings indicate that for a reliable and comparable measurement of spasticity, an exact description of test position and procedure is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
(21 reference statements)
1
22
0
Order By: Relevance
“…These results emphasize the speed control gain using an isokinetic machine, whereas it is not possible to control the velocity when using the MAS in routine clinical practice. 16 We found higher torque values for extension movement than flexion, in agreement with Kakebeeke et al, 17 and a greater excitability of the flexor than the extensor muscles, as expressed by the EMG activation. These data were probably related to the patient's position during the isokinetic test.…”
Section: Assessment Of Hypertonus In Traumatic Sci Individuals a Gripsupporting
confidence: 77%
“…These results emphasize the speed control gain using an isokinetic machine, whereas it is not possible to control the velocity when using the MAS in routine clinical practice. 16 We found higher torque values for extension movement than flexion, in agreement with Kakebeeke et al, 17 and a greater excitability of the flexor than the extensor muscles, as expressed by the EMG activation. These data were probably related to the patient's position during the isokinetic test.…”
Section: Assessment Of Hypertonus In Traumatic Sci Individuals a Gripsupporting
confidence: 77%
“…The range of motion (ROM) was equally defined for both positions so that we could test extensors and flexors of the knee at different lengths. As was shown in an earlier work of the same group, 17 the knee extensors are prestretched in the lying position and therefore spasticity is easily elicited. On the other hand, the knee flexors are prestretched in the sitting position and therefore in this position more excitable.…”
Section: Methodsmentioning
confidence: 68%
“…17 As far as the subjective feelings of the subjects are concerned, six out of 10 indicated they would be less spastic after cycling and, three subjects out of 10 indicated they would be less spastic after the break of half an hour (Table 5). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and validity of isokinetic dynamometers (Kin-Com s , Cybex) has been examined in several studies, [37][38][39][40][41][42] from which it can be concluded that the resistive force values are highly reproducible for lowas well as high-angle velocities, and in able bodied as well as in individuals with cerebral palsy and SCL (Table 4).…”
Section: Reliability Of Isokinetic Dynamometer Measurementsmentioning
confidence: 99%